Indirect evidence for proton pump inhibitor failure in patients taking them independent of meals - Freigofas, Julia; Haefeli, Walter E.; Brenner, Hermann; Quinzler, Renate (Pharmacoepidemiology and drug safety, 2014)
Purpose: We investigated the association between conditions of proton pump inhibitor (PPI) treatment failure and food intake in an elderly ambulatory population. Methods: Our data originate from a large population-based cohort study. During a home visit done by a trained study physician, patients were asked for each medication to state whether it was taken in relation to a meal (before, concurrently with, and after) or independent of a meal. This information was analyzed for all patients taking a PPI daily and correlated to markers of PPI failure. Results: Out of 2717 patients participating in a home visit and taking at least one medication, 383 took a PPI daily (14.1%). A PPI intake independent of meals was defined as incorrect and was observed in 64 patients, whereas 319 patients took their PPI in relation to a meal, which was defined as the correct intake. Treatment failure was observed in 10 out of 64 (15.6%) PPI users with incorrect intake and in 18 out of 319 (5.6%) PPI users with correct intake. The risk of treatment failure was threefold higher in patients taking their PPI independent of meals (OR 3.35; 95%CI 1.44-7.76). Conclusion: The higher risk for PPI failure in patients taking PPIs independent of meals suggests that synchronized PPI administration with meals is indeed essential, and better counseling of patients is needed.
Gesehen am 20.08.2020